1999
DOI: 10.1002/(sici)1097-010x(19990601)283:7<620::aid-jez2>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Calcium homeostasis in crustacea: The evolving role of branchial, renal, digestive and hypodermal epithelia

Abstract: Crustaceans serve as an ideal model for the study of calcium homeostasis due to their natural molting cycle. Demineralization and remineralization of the calcified cuticle is accompanied by bidirectional Ca transfer across the primary Ca transporting epithelia: gills, antennal gland (kidney), digestive system, and cuticular hypodermis. The review will demonstrate how a continuum of crustaceans can be used as a paradigm for the evolution of Ca transport mechanisms. Generally speaking, aquatic crustaceans rely p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
2
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(45 citation statements)
references
References 121 publications
0
38
2
5
Order By: Relevance
“…Overall, the comparison of both populations under 380 ppm CO 2 revealed that Svalbard Megalopae during the first 14 days at 3°C could not set their calcification rate to the same level as Megalopae from Helgoland at the same temperature. Possibly, enzymes and transporters supporting the active influx of calcium ions and their assembly into the chitin layer (Giraud 1981;Neufeld and Cameron 1993;Wheatly 1999) differ in their expression or activity between both populations. Alternatively, energy allocation to calcification may be less in the population from Svalbard and thereby delay the accumulation of carbonates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the comparison of both populations under 380 ppm CO 2 revealed that Svalbard Megalopae during the first 14 days at 3°C could not set their calcification rate to the same level as Megalopae from Helgoland at the same temperature. Possibly, enzymes and transporters supporting the active influx of calcium ions and their assembly into the chitin layer (Giraud 1981;Neufeld and Cameron 1993;Wheatly 1999) differ in their expression or activity between both populations. Alternatively, energy allocation to calcification may be less in the population from Svalbard and thereby delay the accumulation of carbonates.…”
Section: Discussionmentioning
confidence: 99%
“…For mineralizing the matrix of the cuticle, calcium is transported to the extracellular space through the apical membrane by Ca 2? -ATPase (Wheatly 1999 (Neufeld and Cameron 1993;Wheatly 1999). Here, calcium and carbonate combine to form CaCO 3 (Cameron 1985a, b), which is precipitated to the chitin-protein fibres of the exo-and epicuticle (Travis 1955).…”
Section: Introductionmentioning
confidence: 99%
“…The calcium budget of lobsters is highly dynamic, and is tightly coupled to their moult cycle, growth and to environmental conditions (Zhuang & Ahearn 1996, 1998, Klein & Ahearn 1999, Wheatly 1999, Flik & Haond 2000. These mechanisms are normally used to regulate intra-and extracellular calcium concentrations and to rapidly translocate calcium across epithelia during the moulting cycle (Wheatly 1999).…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms are normally used to regulate intra-and extracellular calcium concentrations and to rapidly translocate calcium across epithelia during the moulting cycle (Wheatly 1999). During the cycle, mineral calcium is usually stored in intracellular phosphate-storage granules and in extracellular gastroliths in the stomach , Wheatly 1999.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation